Dual Localization of Squalene Epoxidase, Erg1p, in Yeast Reflects a Relationship between the Endoplasmic Reticulum and Lipid Particles - Leber, Regina (The American Society for Cell Biology, 1998)
Squalene epoxidase, encoded by the ERG1 gene in yeast, is a key enzyme of sterol biosynthesis. Analysis of subcellular fractions revealed that squalene epoxidase was present in the microsomal fraction (30,000 × g) and also cofractionated with lipid particles. A dual localization of Erg1p was confirmed by immunofluorescence microscopy. On the basis of the distribution of marker proteins, 62% of cellular Erg1p could be assigned to the endoplasmic reticulum and 38% to lipid particles in late logarithmic-phase cells. In contrast, sterol Δ(24)-methyltransferase (Erg6p), an enzyme catalyzing a late step in sterol biosynthesis, was found mainly in lipid particles cofractionating with triacylglycerols and steryl esters. The relative distribution of Erg1p between the endoplasmic reticulum and lipid particles changes during growth. Squalene epoxidase (Erg1p) was absent in an erg1 disruptant strain and was induced fivefold in lipid particles and in the endoplasmic reticulum when the ERG1 gene was overexpressed from a multicopy plasmid. The amount of squalene epoxidase in both compartments was also induced approximately fivefold by treatment of yeast cells with terbinafine, an inhibitor of the fungal squalene epoxidase. In contrast to the distribution of the protein, enzymatic activity of squalene epoxidase was only detectable in the endoplasmic reticulum but was absent from isolated lipid particles. When lipid particles of the wild-type strain and microsomes of an erg1 disruptant were mixed, squalene epoxidase activity was partially restored. These findings suggest that factor(s) present in the endoplasmic reticulum are required for squalene epoxidase activity. Close contact between lipid particles and endoplasmic reticulum may be necessary for a concerted action of these two compartments in sterol biosynthesis.